Synthesis and characterization of activated carbon based on young coconut fiber as a supercapacitor electrode - Nasution, Dio Davana Firdaus; Awitdrus, Awitdrus (Indonesian Physics Communication, 2024)
Supercapacitor is energy storage devices consisting of electrodes, electrolyte, current collectors, and separator. In this research, carbon electrodes are made from young coconut fiber biomass (SKM) waste using ZnCl2 0.5 M as activation agent and variations in  physical activation temperatures. Carbon electrodes preparation begins with a pre-carbonized process of 200ºC temperatures for 1 hour and 30 minutes,  chemical activation using ZnCl2 0.5 M as activation agent, then the carbonization process uses N2 gas as well as physics activation using CO2 in temperature variation of 700ºC, 750ºC, and 800ºC. Analysis of the nature of electrodes cell capacitor based fiber young coconut fibers sample shows that the activation physics 750ºC sample is best, agreeble with the density of carbon electrodes declined by 40.43% after the carbonization-activation process. Carbon electrodes represent semicrystalline based on the characterization of the X-ray diffraction, marked with a ramp peak at 2θ at about 24º and 45º. The SKM-750 has a highest of Lc/La ratio an average number of microcrystalline inner layers (Np), are 0.9 and 3.55. SKM-750 has the highest of specific capacitance value, namely 245.45 F/g.